Comparative study of antimicrobial activity of composite semisolid dosage forms for differentiated therapy of foot mycosis - V. V. Luts; N. L. Коlycheva; V. V. Gladyshev (Zaporozhye State Medical University, 2018)
Abstract The aim of work is the study of antimicrobial activity of composite semisolid dosage forms for differentiated therapy of foot mycosis with 2-mercaptobenzthiazol and chinozol, namely the paste on emulsive base and the ointment on hydrophilic delivery vehicle. Materials and methods. As the objects of investigation, the paste on emulsive base and the ointment on methylcellulose glycerogel, providing optimal releasing of 2-mercaptobenzthiazol and chinozol from the delivery vehicle and also appropriate semisolid dosage forms (placebo) were used. Antimicrobial activity of paste for nails, ointment for external use and their delivery vehicle was determined for Candida albicans fungi by diffusion into agar method. Candida albicans fungi take second place by the frequency of foot mycosis occurrence after dermatophytes and gram-positive (Staphylococcus aureus), gram-negaitive (Pseudomonas aeruginosa) pathogenic bacteria because of high frequency of mixtinfection joining the foot mycosis. As the references the well-known antimycotic medications which are registered in Ukraine and for enough time have been used in practice of foot mycosis therapy - cream "Clotrimazole 1 %" (Salutas Pharma, Germany), cream "Exoderil 1 %" (GlaxoSmithKline Pharmaceuticals S.A., Poland), ointment "Kanespor 1 %" (Kern Pharma S.L., Spain) were used. Results. It was revealed that investigated pharmacotherapeutic medicines are characterized by high efficacy for above mentioned microflora. Bases of experimental dosage form have a moderate antimycotic and antibacterial activity caused by onycholytics (salicylic and benzoic acids) and keratolytic (carbamide) presence in formulations. In comparative microbiological studies it was established that the experimental paste for onychomycosis therapy, which contains the composition of nonspecific antimycotics and onycholytics, noticeably surpasses one of the most effective medications - ointment "Kanespor" by the area of growth inhibition zone for pathogenic fungi Candida albicans and gram-negaitive bacteria Escherichia coli and Pseudomonas aeruginosa. It was revealed that by the diameter of growth inhibition zone for above mentioned microorganisms the developed ointment surpasses such modern remedies as cream "Clotrimazole 1 %" and cream "Exoderil 1 %", which are widely used in topical treatment of dermatological mycosis. Conclusions. Obtained results of antimicrobial activity study of composite semisolid dosage forms for differentiated therapy of foot mycosis on the base of combination of 2-mercaptobenzthiazol and chinozol allow to predict their high clinical value and possibility of providing the domestic dermatology with affordable and effective pharmacotherapeutic medicines, creating the real alternative to import products.